Challenges of Using Videos in Exam Rooms of Safety-Net Clinics to Encourage Patient Self-Disclosure of Intimate Partner Violence and to Increase Provider Screening - Tavrow, Paula (Violence against women, 2021)
Identifying intimate partner violence (IPV) in clinics allows for early intervention. We tested a comprehensive approach in five safety-net clinics to encourage female victims to self-identify and providers to screen. The main components were (a) short, multilingual videos for female patients; (b) provider training; and (c) management tools. Although videos were viewed 2,150 times, only 9% of eligible patients watched them. IPV disclosure increased slightly (6%). Lack of internal champions, high turnover, increased patient load, and technological challenges hindered outcomes. Safety-net clinics need feasible methods to encourage IPV screening. Management champions and IT support are essential for video-based activities.